Effects of alcoholic fermentation on the non-volatile and volatile compounds in grapefruit (Citrus paradisi Mac. cv. Cocktail) juice: A combination of UPLC-MS/MS and gas chromatography ion mobility spectrometry analysis - Cao, Xuedan; Ru, Shuijiang; Fang, Xiugui; Li, Yi; Wang, Tianyu; Lyu, Xiamin (Frontiers in Nutrition, 2022)
Grapefruit has attracted much attention as a functional fruit, of which ‘Cocktail’ is a special variety with low acidity. The present study aimed to investigate the effects of alcoholic fermentation on the functional characteristics and volatile profiles of ‘Cocktail’ grapefruit juice. To analyze, a non-targeted metabolomics method based on UPLC-MS/MS and volatiles analysis using GC-IMS were performed. A total of 1015 kinds of phytochemicals were identified, including 296 kinds of flavonoids and 145 kinds of phenolic acids, with noticeably increasing their varieties and abundance following the fermentation. Also, 57 kinds of volatile compounds were detected, and alcoholic fermentation was effective in modulating aromatic profiles of grapefruit juice, with terpenes and ketones decreasing, and alcohols increasing together with esters. These results indicate that alcoholic fermentation could enrich ‘Cocktail’ grapefruit juice flavor and enhance its nutritional health value, which provides a wealth of information for the development of fermented grapefruit beverages.